2009
DOI: 10.1051/0004-6361/200810422
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray spectral evolution of Cygnus X-2 in the framework of bulk Comptonization

Abstract: Context. Strong theoretical and observational support exists that the spectral evolution of neutron-star LMXBs, including transient hard X-ray tails, can be explained by the interplay between thermal and bulk motion Comptonization. The introduction of a new XSPEC Comptonization model, Comptb, including thermal and bulk Comptonization, has provided additional support to this interpretation. Aims. We used Comptb to investigate the spectral evolution of the neutron-star LMXB Cyg X-2 along its Z track. We selected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Cowley et al (1979) reported that Cyg X-2 is observed at an inclination between 65 • -75 • . Farinelli et al (2009) analyzing BeppoSAX observations of Cyg X-2 and using a sum of two COMPTB components, successfully described the spectral behavior of the source from its HB to NB. Consequently we can suggest that modulation of the flux from the TL outer part and TL innermost part (related to N Com1 and N Com2 , respectively) is a result of geometric effects.…”
Section: Does Mass Accretion Rate Monotonically Increase During Hb→nbmentioning
confidence: 99%
“…Cowley et al (1979) reported that Cyg X-2 is observed at an inclination between 65 • -75 • . Farinelli et al (2009) analyzing BeppoSAX observations of Cyg X-2 and using a sum of two COMPTB components, successfully described the spectral behavior of the source from its HB to NB. Consequently we can suggest that modulation of the flux from the TL outer part and TL innermost part (related to N Com1 and N Com2 , respectively) is a result of geometric effects.…”
Section: Does Mass Accretion Rate Monotonically Increase During Hb→nbmentioning
confidence: 99%
“…However, to explain the high energy power-law tail by thermal Comptonization, the required electron medium temperature is ∼100 keV and the optical depth around unity (Parker, et al, 2016, Titarchuk et al, 2014. Mainly, three models are proposed for power-law tail in context of Comptonization, i) non-thermal Comptonization (Done & Kubota, 2006, Kubota & Done, 2016 ii) hybrid Comptonization model (Coppi, 1999, Gierlinski et al, 1999 iii) bulk Comptonization model (Farinelli et al, 2009, Paizis et al, 2006, Titarchuk et al, 1997. In bulk Comptonization, the soft photons are upscattered by high energetic electrons, which have both thermal and bulk motions.…”
Section: Introductionmentioning
confidence: 99%
“…In bulk Comptonization, the soft photons are upscattered by high energetic electrons, which have both thermal and bulk motions. For bulk region, Titarchuk et al (1997) had considered a free-fall converging flow of spherically accreted plasma into BH (later, a bulk Comptonization model was also developed for NS with a similar free-fall bulk region, see, e.g., Farinelli et al, 2009). However, a spherically free-fall region into BH was first proposed by Chakrabarti & Titarch (1995) to examine the HS state in BH XRBs.…”
Section: Introductionmentioning
confidence: 99%
“…Di Salvo et al 2006), or on bulk motion of matter near the compact object (e.g. Paizis et al 2006;Farinelli et al 2009). In order to distinguish between these models one need to obtain high quality spectral energy distribution in hard X-rays because of pos-sible high energy cutoff, predicted by some models, and to relate the behaviour of the hard X-ray tail to other components of X-ray emission of the source.…”
Section: Introductionmentioning
confidence: 99%